COVID-19 Induced Cardiomyopathy Successfully Treated with Tocilizumab. (6th April 2022) - Schreiber, Ariyon; Elango, Kalaimani; Soussu, Chris; Fakhra, Sadaf; Asad, Shabada; Ahsan, Chowdhury
Abstract : Background . Currently, the literature regarding the management of COVID-19 induced cardiomyopathy with reduced ejection fraction is limited. In this case report, we present the first documented case of COVID-19 induced myocardial stunning leading to severely reduced LV systolic function that was reversed by the administration of corticosteroids and tocilizumab. Case Summary . A 39-year-old female with well controlled systemic hypertension, tested positive for SARS-CoV-2 RNA and underwent self-isolation for 14 days. Patient presented to our facility a month later with one-week history of progressively worsening generalized body aches, chills, fever, watery diarrhea, nausea with associated mild dry nonproductive cough, shortness of breath and nonspecific chest pain. Initial labs demonstrated that she was COVID-19 positive, elevated troponin (4.295 ng/ml), and elevated BNP (2, 291 pg/ml). Her initial Transthoracic echocardiography demonstrated an Left ventricular ejection fraction (LVEF) of 20-25% with apical akinesis. After administration of tocilizumab and corticosteroids, patient demonstrated interval improvement with LVEF improving to 50-55% within days. Her labs confirmed these findings with improved troponin (0.858 ng/ml) and BNP (209 pg/ml). Discussion . This case demonstrates that it can be safe and efficacious to use tocilizumab and corticosteroids in patients with COVID-19 induced cardiomyopathy. These finding suggest that cytokine storm is the predominant mechanism by which COVID-19 induced cardiomyopathy occurs. Additional studies are required to determine the role of corticosteroids and tocilizumab in management of this condition.